Effect of screen time and physical activity on the mental health of students - Waisul Quroni Azim; Nanik Indahwati; Waisul Quroni Azim; Nanik Indahwati (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2026)
Screen time has become an inseparable part of adolescents' lives in the digital era. Excessive screen time may affect mental health, while physical activity is often neglected as a result of this lifestyle. This study aims to analyse the influence of screen time duration and physical activity on the mental health of students at SMP Labschool UNESA 3. The research used a quantitative method with a correlational approach. The sample consisted of 90 students from grades 7 to 9, selected through random sampling. Data were collected using validated questionnaires covering screen time duration, physical activity level, and mental health based on the Mental Health Quality of Life (MHQoL) instrument. Data analysis was conducted using the Generalized Linear Model (GLM). The results showed that screen time duration and physical activity did not significantly affect students' mental health (p > 0.05). Most respondents demonstrated good to very good mental health conditions, although a small number of students were in the neutral to less favourable categories. The full model did not significantly improve on the intercept-only model (Omnibus test, p = 0.280), and the form of play (PB1) was the predictor closest to, though it did not reach, the significance threshold (p = 0.073), suggesting it warrants further investigation. Rather than duration alone, the findings underline the importance of attending to the type and quality of both screen-based and physical activities in supporting students' mental health.